Ranunculus platensis (Ranunculaceae). New record for the flora of La Pampa province, Argentina (Semiárida, 2018)
Plant specimens were collected at the field from a mixed crop-livestock farm nearby Santa Rosa city (La Pampa, Argentina), whose identity was confirmed as Ranunculus platensis Spreng after taxonomic analysis. This finding constitutes the first record of such species for La Pampa province, revealing that its spatial distribution is becoming wider in Argentina.DOI: http://dx.doi.org/10.19137/semiarida.2017(01).41-44
Keywords: Ranunculaceae; flora of the pampas; biodiversity